Characterization of a Novel Model of Chronic Migraine - Pradhan, Amynah A (2013)
Chronic migraine is a disabling condition that affects hundreds of millions of individuals worldwide. The development of novel migraine treatments has been slow, in part due to a lack of predicative animal models. We have developed a new model of chronic migraine involving the use of nitroglycerin, a known migraine trigger in humans. Chronic intermittent administration of nitroglycerin to mice resulted in acute mechanical hyperalgesia with each exposure as well as a progressive and sustained basal hyperalgesia. This chronic basal hyperalgesia occurred in a dose-dependent fashion and persisted for days following cessation of NTG administration. NTG-evoked hyperalgesia was exacerbated by the phosphodiesterase 5 inhibitor sildenafil, also a human migraine trigger, consistent with nitric oxide as a primary mediator of this hyperalgesia. The acute but not the chronic basal hyperalgesia was significantly reduced by the acute migraine therapy sumatriptan, whereas both the acute and chronic hyperalgesia was significantly attenuated by the migraine preventive therapy topiramate. Chronic NTG-induced hyperalgesia is a mouse model that may be useful for the study of mechanisms underlying progression of migraine from an episodic to a chronic disorder, and for the identification and characterization of novel acute and preventive migraine therapies.